2021
DOI: 10.1039/d0ew00819b
|View full text |Cite
|
Sign up to set email alerts
|

Growth ofLegionelladuring COVID-19 lockdown stagnation

Abstract: While “avoiding stagnation” has been the mantra of many building water quality experts, the foundational support for how this terminology is used in peer-reviewed publications and building water management guidelines...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Stagnation as a catch-all term for water aging is problematic because it can occur at a single outlet or an entire system, for hours to years, and is coincident with many biotic and abiotic water quality changes that occur to different extents within or among different systems [ 8 ]. In this study, we specifically reserve the term “stagnation” to describe the lack of water demand and flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stagnation as a catch-all term for water aging is problematic because it can occur at a single outlet or an entire system, for hours to years, and is coincident with many biotic and abiotic water quality changes that occur to different extents within or among different systems [ 8 ]. In this study, we specifically reserve the term “stagnation” to describe the lack of water demand and flow.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent contradictions in the impact of stagnation are complicated by the all-encompassing nature in which the term is typically used [ 8 ]. “Stagnation” has been used to describe a range of plumbing conditions including no water flow or exchange [ 1 ], existence of dead-end pipes [ 9 ], intermittent use at individual outlets [ 7 ], and generally elevated water residence time caused by low water demand and/or over-sized components [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Water stagnation is known to be a critical factor for water-quality decrease, with an inherent impact on Legionella prevalence [93]. For example, De Giglio et al [59] assessed the microbiological water quality in an Italian hospital over 3 months during the COVID-19 lockdown.…”
Section: Water Stagnation Vs Water Flushingmentioning
confidence: 99%
“…The authors found higher concentrations of L. pneumophila after the lockdown, which was attributed to building inoccupation. The work of Rhoads et al [93] provides an interesting overview of the complex topic of water stagnation related to Legionella management. One of the strategies to minimize stagnation problems is water flushing.…”
Section: Water Stagnation Vs Water Flushingmentioning
confidence: 99%
“…Stagnant water can have chemical and microbiological contaminants that pose potential health risks to occupants [80] . In particular, water stagnation in buildings may lead to Legionella growth, but study on the relationship between Legionnaires' disease cases and COVID-19 lockdowns is still limited [81] . This should be considered to ensure the safety building water system and devices when reopening buildings.…”
Section: State Of the Knowledge And Research Needsmentioning
confidence: 99%